2011
DOI: 10.1074/jbc.m110.209528
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Phosphophoryn Is Sufficient for the Induction of Matrix Mineralization by Mammalian Cells

Abstract: Mineralized tissues such as dentin and bone assemble extracellular matrices uniquely rich in a variety of acidic phosphoproteins. Although these proteins are presumed to play a role in the process of biomineralization, key questions regarding the nature of their contributions remain unanswered. First, it is not known whether highly phosphorylated proteins alone can induce matrix mineralization, or whether this activity requires the involvement of other bone/dentin non-collagenous proteins. Second, it remains t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…The intensity of binding at a molar ratio of 1 to 1 rather than at electrostatic equivalence suggested that a non-electrostatic binding was involved at the primary specific interaction site, emphasizing the probable specificity in DPP sequence responsible for its primary collagen localization. Though polyAsp can do the in vitro job of nucleating cAp, the evidence is strong that, although the sequence of DPP contains approximately 40% Asp residues, the phosphorylation of the Ser residues of DPP ( 50% of the amino acids) is crucial for its function in mediating mineralization [42] and, most recently, it has been shown that the introduction of a DPP cDNA into a non-mineralizing fibroblast cell leads to expression and secretion of phosphorylated DPP and the induction of HAp mineralization in the fibroblast cultures [43]. …”
Section: Sibling Proteins and Their Interaction With Collagen Fimentioning
confidence: 99%
“…The intensity of binding at a molar ratio of 1 to 1 rather than at electrostatic equivalence suggested that a non-electrostatic binding was involved at the primary specific interaction site, emphasizing the probable specificity in DPP sequence responsible for its primary collagen localization. Though polyAsp can do the in vitro job of nucleating cAp, the evidence is strong that, although the sequence of DPP contains approximately 40% Asp residues, the phosphorylation of the Ser residues of DPP ( 50% of the amino acids) is crucial for its function in mediating mineralization [42] and, most recently, it has been shown that the introduction of a DPP cDNA into a non-mineralizing fibroblast cell leads to expression and secretion of phosphorylated DPP and the induction of HAp mineralization in the fibroblast cultures [43]. …”
Section: Sibling Proteins and Their Interaction With Collagen Fimentioning
confidence: 99%
“…However, recently, DPP has been shown to possess signaling functions that can initiate lineage specific differentiation of mesenchymal stem cells (29). DPP in the ECM can mediate cell adhesion and initiate integrin mediated signaling (30,31).…”
Section: Dentin Phosphophoryn (Dpp)mentioning
confidence: 99%
“…Murshed et al also showed fibroblasts could mineralize when tissue non-specific alkaline phosphatase was over-expressed and -glycerol phosphate was added, but since alkaline phosphatase and -glycerol phosphate generate mineral in the absence of a matrix [63], the fibroblast data does not prove that physiologic mineralization was taking place. On the other hand, without alkaline phosphatase and without an organic phosphate source, Sfeir et al have induced physiologic HA formation in fibroblasts that do not mineralize under control conditions, by inserting the gene for a dentin-specific protein, phosphophoryn [64]. Thus, it appears that collagen-based tissues can support mineralization with the right additional factors, but what factors are they -and which are essential?…”
Section: The Importance Of Local Phosphate Concentrationsmentioning
confidence: 99%